Recurrent DNMT3A R882 mutations in Chinese patients with acute myeloid leukemia and myelodysplastic syndrome. - Jiang Lin; Dong-ming Yao; Jun Qian; Qin Chen; Wei Qian; Yun Li; Jing Yang; Cui-zhu Wang; Hai-yan Chai; Zhen Qian; Gao-fei Xiao; Wen-rong Xu (PLoS ONE, 2011)
Somatic mutations of DNMT3A gene have recently been reported in acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). We examined the entire coding sequences of DNMT3A gene by high-resolution melting analysis and sequencing in Chinese patients with myeloid malignancies. R882 mutations were found in 12/182 AML and in 4/51 MDS, but not in either 79 chronic myeloid leukemia (CML), or 57 myeloproliferative neoplasms (MPNs), or 4 chronic monomyelocytic leukemia. No other DNMT3A mutations were detected in all patients. R882 mutations were associated with old age and more frequently present in monoblastic leukemia (M4 and M5, 7/52) compared to other subtypes (5/130). Furthermore, 14/16 (86.6%) R882 mutations were observed in patients with normal karyotypes. The overall survival of mutated MDS patients was shorter than those without mutation (median 9 and 25 months, respectively). We conclude that DNMT3A R882 mutations are recurrent molecular aberrations in AML and MDS, and may be an adverse prognostic event in MDS.